The Effect of the Proportion of the Board of Commissioners, Audit Committee, Asymmetric Information and Company Size on Earnings Management Practices - Ridho, Muhammad; Djamil, Nasrullah (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
The objective of this study was to empirically determine whether there is a correlation between the proportion of the board of commissioners, audit committee, information asymmetry, and company size with earnings management in the consumer goods manufacturing companies sector listed on the Indonesia Stock Exchange during the years 2010-2012. The study aims to clarify any potential links between the identified variables. Data was extracted from the financial statements of each sample company, which were publicly available on the websites www.idx.co.id and ICMD. The study employed purposive sampling, gathering data from 15 companies over a period of three years, resulting in a total of 45 observations. The independent variables include the proportion of the board of commissioners, audit committee, information asymmetry, and company size, while earnings management serves as the dependent variable. The findings from our study utilizing panel data and regression models demonstrate that neither the proportion of the board of commissioners, audit committee, information asymmetry, nor company size have any impact on earnings management either partially or concurrently.